2017
DOI: 10.1159/000471788
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Nocardiosis Simulating Cutaneous Lymphatic Sporotrichosis

Abstract: Sporotrichosis is the subcutaneous mycosis caused by several species of the Sporothrix genus. With worldwide occurrence, the State of Rio de Janeiro is presently undergoing a zoonotic sporotrichosis epidemic. The form of lymphocutaneous nocardiosis is rare, being caused especially by Nocardia brasiliensis. It appears as a nodular or ulcerated lesion, with multiple painful erythematous nodules or satellite pustules distributed along the lymphatic tract, similar to the lymphocutaneous variant of sporotrichosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Another transmission route is through infected animals. 5,7,8 So far, there have been only two cases reported in China of lymphocutaneous nocardiosis caused by N. brasiliensis in immunocompetent patients. One was reported by Chu et al 10 in 2017 and occurred in an 87-year-old woman following a wasp sting.…”
Section: Discussionmentioning
confidence: 99%
“…Another transmission route is through infected animals. 5,7,8 So far, there have been only two cases reported in China of lymphocutaneous nocardiosis caused by N. brasiliensis in immunocompetent patients. One was reported by Chu et al 10 in 2017 and occurred in an 87-year-old woman following a wasp sting.…”
Section: Discussionmentioning
confidence: 99%
“…7 Nocardia species are gram-positive, rod-shaped bacteria, which are partially acid-fast beaded branching filaments that grow under aerobic conditions. 10 N brasiliensis and N pseudobrasiliensis can be distinguished from the other species by adenine hydrolysis and nitrate reductases, but these tests are not commonly available in most microbiology laboratories. Therefore, matrix-assisted laser desorption ionization-time of flight mass spectroscopy and gene sequence analysis are used for species identification as was seen in our case.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocompetent patient with cutaneous nocardiosis should be ideally treated with trimethoprim-sulfamethoxazole for 2 to 4 months, which may need to be extended further for some immunocompromised patients to prevent recurrence. 10…”
Section: Discussionmentioning
confidence: 99%
“…The present authors' patient formed the lesion from the insect bite. So far, there are only four cases in the world of primary cutaneous nocardiosis caused by N. brasiliensis induced by insect bites (Chu et al, 2017;O'Connor & Dire, 1992;Paredes et al, 1999;Secchin et al, 2017). In china, Chu et al (2017) reported an 87-year-old female patient who presented painful erythema on her right forearm following a wasp sting, and rapidly deteriorated.…”
Section: Discussionmentioning
confidence: 99%
“…Both Gram staining and Anti-acid staining showed positive branching bacterium (Figure 1d is not common to primary cutaneous nocardia infection in immunecompetent host. N. brasiliensis is the most common species that causes skin infection especially in lymphocutaneous nocardiosis type (Ayoade, Mada, Joel Chandranesan, & Alam, 2018;Secchin et al, 2017;Wilson, 2012). Lymphocutaneous nocardiosis, also called lymphocutaneous type, may resemble sporotrichosis clinically and easy to misdiagnose (Ayoade et al, 2018;Bryant, Davis, Kucenic, & Mark, 2010;Secchin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%